Autoimmune gastrointestinal complications in patients with systemic lupus erythematosus: case series and literature review. (December 2016) - Alves, S Custódio; Fasano, S; Isenberg, D A
The association of systemic lupus erythematosus (SLE) with gastrointestinal autoimmune diseases is rare, but has been described in the literature, mostly as case reports. However, some of these diseases may be very severe, thus a correct and early diagnosis with appropriate management are fundamental. We have analysed our data from the SLE patient cohort at University College Hospital London, established in 1978, identifying those patients with an associated autoimmune gastrointestinal disease. We have also undertaken a review of the literature describing the major autoimmune gastrointestinal pathologies which may be coincident with SLE, focusing on the incidence, clinical and laboratory (particularly antibody) findings, common aetiopathogenesis and complications.